A mutational and molecular dynamics study of the cys-loop GABA receptor Hco-UNC-49 from Haemonchus contortus: Agonist recognition in the nematode GABA receptor family. Issue 3 (December 2018) - Foster, Josh; Cochrane, Everett; Khatami, Mohammad Hassan; Habibi, Sarah A.; de Haan, Hendrick; Forrester, Sean G.
Abstract: The UNC-49 receptor is a unique nematode γ-aminobutyric acid (GABA)-gated chloride channel that may prove to be a novel target for the development of nematocides. Here we have characterized various charged amino acid residues in and near the agonist binding site of the UNC-49 receptor from the parasitic nematode Haemonchus contorts . Utilizing the Caenorhabditis elegans GluCl crystal structure as a template, a model was generated and various charged residues [D83 (loop D), E131 (loop A), H137 (pre-loop E), R159 (Loop E), E185 (Loop B) and R241 (Loop C)] were investigated based on their location and conservation. These residues may contribute to structure, function, and molecular interactions with agonists. It was found that all residues chosen were important for receptor function to varying degrees. Results of the mutational analysis and molecular simulations suggest that R159 may be interacting with D83 by an ionic interaction that may be crucial for general GABA receptor function. We have used the results from this study as well as knowledge of residues involved in GABA receptor binding to identify sequence patterns that may assist in understanding the function of lesser known GABA receptor subunits from parasitic nematodes. Graphical abstract: Image 1 Highlights: Key functional residues were investigated in the Hco-UNC-49 receptor. A glutamic acid in the binding pocket (loop B) is essential for agonist recognition. Interaction between residues in different binding loops are important for function.